Acute phase proteins, hematological and serum biochemical profiles of female dogs in diestrus, mucometra and pyometra - Friolani, M. [UNESP]; Santana, A. M.; Voorwald, F. A.; Almeida, L. A.; Padilha-Nakaghi, L. C. [UNESP]; Silva, D. G. [UNESP]; Costa, I. B.; Fagliari, J. J. [UNESP]; Toniollo, G. H. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
Blood samples from 200 female dogs divided into 6 groups (diestrus, mucometra, pyometra) were evaluated, with the pyometra group categorized according to the ASA classification (American Society of Anesthesiologists), that is, from ASA II to V, totaling six groups. Aiming to analyze the acute phase proteins (APP), hematological and serum biochemical profiles of the female dogs in the study, establishing the differential diagnosis and prognosis according to the group. The SDS-PAGE method was used for protein fractionation, complete blood count using an automated hematological analyzer and histogram, biochemical tests performed using a semi-automatic spectrophotometer and measurement of serum concentrations of sodium and ionic calcium using the selective ion method. The results showed that female dogs with pyometra categorized in the ASA II to V classification revealed biochemical alterations between the study groups, as well as the acute phase proteins, presented variations according to the systemic involvement, degree of inflammatory response and ASA classification of the female dogs with pyometra, in which ceruloplasmin (p=0.07) and transferrin (p=0.07) did not show statistical significance, but showed an increase in their concentration according to the inflammatory evolution, albumin (p<0.0001), IgGCP (p <0.0001), haptoglobin (p<0.0001), alpha acid glycoprotein (p<0.0001), IgGCL (p<0.0001) and the one identified by its atomic weight 23,000 Da (p=0.0031), enabling the assessment of the acute phase response and aiding in the early detection of the systemic inflammatory response and better therapeutic guidance for the patient.
Keywords: female dog; inflammation; pyometra; acute phase proteins; uterus